Influence of the phenological state of in the antioxidant potential and chemical composition of ageratina havanensis. effects on the p-glycoprotein function - García, Trina H.; Da Rocha, Claudia Quintino; Delgado-Roche, Livan; Rodeiro, Idania; Ávila, Yaiser; Hernández, Ivones; Cuellar, Cindel; Lopes, Miriam Teresa Paz; Vilegas, Wagner [UNESP]; Auriemma, Giulia; Spengler, Iraida; Rastrelli, Luca (MDPI, 2020)
Ageratina havanensis (Kunth) R. M. King & H. Robinson is a species of flowering shrub in the family Asteraceae, native to the Caribbean and Texas. The aim of this work was to compare the quantitative chemical composition of extracts obtained from Ageratina havanensis in its flowering and vegetative stages with the antioxidant potential and to determine the effects on P-glycoprotein (P-gp) function. The quantitative chemical composition of the extracts was determined quantifying their major flavonoids by UPLC-ESI-MS/MS and by PCA analysis. The effects of the extracts on P-gp activity was evaluated by Rhodamine 123 assay; antioxidant properties were determined by DPPH, FRAP and inhibition of lipid peroxidation methods. The obtained results show that major flavonoids were present in higher concentrations in vegetative stage than flowering stage. In particular, the extracts obtained in the flowering season showed a significantly higher ability to sequester free radicals compared to those of the vegetative season, meanwhile, the extracts obtained during the vegetative stage showed a significant inhibitory effect against brain lipid peroxidation and a strong reductive capacity. This study also showed the inhibitory effects of all ethanolic extracts on P-gp function in 4T1 cell line; these effects were unrelated to the phenological stage. This work shows, therefore, the first evidence on: The inhibition of P-gp function, the antioxidant effects and the content of major flavonoids of Ageratina havanensis. According to the obtained results, the species Ageratina havanensis (Kunth) R. M. King & H. Robinson could be a source of new potential inhibitors of drug efflux mediated by P-gp. A special focus on all these aspects must be taking into account for future studies.
Keywords: Ageratina havanensis; Antioxidant potential; Flavonoids; P-glycoprotein; UPLC-ESI-MS/MS